Social networking site adoption in Malaysia and Indonesia - Noor Ismawati Jaafar,; Bobby Darmawan,; Mohd Yahya Mohamed Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study employed the Model of Technology Preference (MTP) to investigate the antecedents of behaviour intention to adopt Social Networking Site (SNS) for communication after considering individual’s preference factor. This study used quantitative approach where surveys were conducted in Malaysia and Indonesia. Self-administered questionnaires were distributed to SNS users in big cities of both countries that lead to a total of 1037 valid responses. The data were analysed using Structural Equation Model (SEM) to measure model fit and to conduct structural modelling. The results in general support that Attribute-Based Preference (ATRP) significantly affects Attitude-Based Preference (ATTP), which also mediates that effect with Behaviour Intention (BI) of using SNS. Nonetheless, the findings from the two countries vary with regard to the attributes that affect the ATTP and the effect of ATTP on BI and Attitude (ATT) towards SNS. Malaysians tend to use SNS for communication due to the availability of options for their preferred technology. This could be explained by the higher pragmatic and masculinity index of the Malaysian culture, which they tend to exhibit in their actions. In contrary, Indonesians tend to defer using the SNS and create another level of attitude before the actual usage.